Scalable dual-layer PVDF loose nanofiltration hollow fiber membranes for treating textile wastewater. (April 2022) - Wang, Chuanfeng; Chen, Yingbo; Hu, Xiaoyu; Guo, Pengfei
Abstract: A dual-layer (DL) PVDF loose nanofiltration (NF) hollow fiber membrane (HFM) with desirable properties was designed via phase inversion process using a continuous online-coating device. By fine-tuning dope formulation and fiber formation, the PVDF coating layer with NF separation capabilities was formed on the shell side of porous matrix-reinforced hollow fiber support while making fiber continuously. The effects of several parameters (e.g., LiCl content, co-solvent ratio (i.e., DMAc:THF) and air-bath distance (evaporation time)) on structures and properties were investigated to manipulate membrane MWCO. It was found that the introduction of volatile co-solvent and the control of evaporation time helped to significantly reduce the PVDF selective layer's thickness. The structure along with performance of the HFM demonstrated the DL ultrafiltration (UF) HFM could be successfully converted into NF HFM only by adjusting the parameters in the production system. After optimizing both phase inversion parameters and coating conditions, the resultant loose NF HFM presented a low MWCO of 1530 Da and a high pure water flux (PWF) of 14.2 L·m −2 ·h −1 ·bar −1 . Meanwhile, the HFM showed competitive dyes rejection (i.e., 99.9% for Rose bengal and Eriochrome black T, 96.5% for Methylene blue) and low NaCl rejection (3.2%). Furthermore, the prepared membrane also presented good stability and high flux recovery during a continuous NF process. This work provided a simple and economical strategy for engineering scalable loose NF HFM for dye purification. Graphical abstract: Unlabelled Image Highlights: The DL PVDF loose NFHFM was designed by online-phase inversion procedure. Fabrication parameters on morphology and performance of HFM were investigated. The introduction of volatile co-solvent helped to reduce the selective layer's thickness remarkably. The membranes exhibited excellent separation performance for textile wastewater.